A Ticking Bomb for Nigeria? The EndSARS Protest in Retrospect - Olaniyan, Taiwo Abimbola; Raheem, Oluwafunminiyi Wasiu (Kashere Journal of Politics and International Relations, 2024)
Since Nigeria’s return to democratic rule in 1999, no social movement has had such a devastating impact across the country as the EndSARS protest in 2020. This protest not only exposed the cracks in the Nigerian nationhood but also reflected leadership failure in the country. The paper presents a retrospect on the EndSARS protest in Nigeria. The analysis is based on keen observations of Nigeria’s socio-political trajectory following the October 2020 demonstration. It incorporates data primarily from secondary sources. This paper contends that serious efforts should be made in pursuit of genuine reforms, social justice and meaningful reconciliation for aggrieved citizens in all strata of the country. The EndSARS protest is not only a ticking time bomb but one of the few opportunities open by the Nigerian political leadership for inclusive governance for the teeming youth population.